2020
DOI: 10.1097/cm9.0000000000001303
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue correlates with sleep disturbances in Parkinson disease

Abstract: Background: Many Parkinson disease (PD) patients complain about chronic fatigue and sleep disturbances during the night. The objective of this study is to determine the relationship between fatigue and sleep disturbances by using polysomnography (PSG) in PD patients. Methods: Two hundred and thirty-two PD patients (152 with mild fatigue and 80 with severe fatigue) were recruited in this study. Demographic information and clinical symptoms were collected. Fatigue severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Fatigue can have several correlations with sleep disturbances in PD as well. One polysomnographic study demonstrated lower percentages of rapid eye movement (REM) sleep in PD patients with severe fatigue compared to those with mild fatigue; in addition, REM sleep behaviour disorder (RBD) was a significant predictor of fatigue in this study [9]. According to a questionnaire-based study which was part of the International Nonmotor Scale validation project, fatigue correlated significantly with depression, anxiety, and sleep dysfunction [10].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Fatigue can have several correlations with sleep disturbances in PD as well. One polysomnographic study demonstrated lower percentages of rapid eye movement (REM) sleep in PD patients with severe fatigue compared to those with mild fatigue; in addition, REM sleep behaviour disorder (RBD) was a significant predictor of fatigue in this study [9]. According to a questionnaire-based study which was part of the International Nonmotor Scale validation project, fatigue correlated significantly with depression, anxiety, and sleep dysfunction [10].…”
Section: Introductionmentioning
confidence: 53%
“…Levodopa may have a beneficial effect on fatigue in PD patients [19]. Higher levodopa equivalent daily dose (LEDD) was noticed in PD patients with fatigue in some studies [9,20], while similarly, LEDD is known to be associated with EDS [21] and RBD [22]. According to one study, patients who received a combination of levodopa/dopamine agonists presented more EDS compared to those under levodopa monotherapy, but no differences were noted regarding fatigue between these two groups [23].…”
Section: Introductionmentioning
confidence: 99%
“…The muscle activity was measured at six locations of the dominant side (GM, BF, VM, AR, ES, RF, SO, and TA) at a frequency of 1,000 Hz. Muscle fatigue estimation for neurological disorders such as hemiplegia (Boudarham et al, 2013(Boudarham et al, , 2014Wang et al, 2017;Mazzoli et al, 2018;Fujita et al, 2020Fujita et al, , 2021, PD (Huang et al, 2017;Palinkas et al, 2019;Cao et al, 2021), MS (Octavia et al, 2015;Porcaro et al, 2019;Stańczyk et al, 2019) has been reported. The approach for EMG-to-muscle force has also been analyzed in Bogey et al (2005).…”
Section: Electromyographymentioning
confidence: 99%
“…Sleep disorder is the most common non-motor symptom in PD, with an incidence of about 47.66% to 89.10% ( Liu et al, 2018 ) and increasing year by year with the course of disease. More and more evidence shows that PD sleep disorders can lead to decreased quality of life ( Zuzuárregui and During, 2020 ), impaired psychosocial and cognitive function ( Riemann, 2019 ), fatigue ( Cao et al, 2020 ), depression ( Demet et al, 1999 ) or substance abuse ( Hasler et al, 2012 ) and may increase the risk of cardiovascular and metabolic diseases ( He et al, 2017 ). In addition to health risks, sleep disorders can also bring significant socio-economic burdens ( Frandsen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%